Retrograde intrarenal surgery using ureteral access sheaths is a safe and effective treatment for renal stones in children weighing <20 kg. Issue 1 (February 2018) - Berrettini, Alfredo; Boeri, Luca; Montanari, Emanuele; Mogiatti, Mirella; Acquati, Pietro; De Lorenzis, Elisa; Gallioli, Andrea; De Marco, Erika Adalgisa; Minoli, Dario Guido; Manzoni, Gianantonio
Summary: Introduction: Surgical treatment of pediatric kidney stones has changed dramatically in recent years because of the miniaturization of surgical instruments and the availability of intracorporeal lithotripters. The retrograde intrarenal surgery (RIRS) technique is nowadays considered an effective and safe procedure but studies in very young children are lacking and use of a ureteral access sheath (UAS) has also been debated. Objective: To assess safety and efficacy of RIRS using UAS in children weighing < 20 kg. Materials and methods: Data from 13 children weighing <20 kg who underwent RIRS for renal stones were collected. A Double-J stent was positioned 14 days before surgery. Demographics, stone location, stone number and composition, stone-free status (SFS) and complications were evaluated. Descriptive statistics were applied to describe the cohort. Results: Thirteen patients, age 3.91 ± 1.8 years (mean ± SD), underwent 16 RIRS. Mean patient weight and stone burden were 14.88 ± 3.81 kg (range 10–20 kg) and 15.5 ± 3.8 mm (median 16 mm), respectively. A UAS was used in 15 out of 16 (93.8%) procedures. SFS was achieved in 81.3% of cases after the first procedure and 100% after auxiliary procedures. Postoperative urinary tract infections with fever (Clavien II) were observed in two (12.5%) patients. Hydrocalyx (Clavien IIIb) was noted in one (6.3%) patient. Patients with stones located in the lower polar calices ( p = 0.024) and with mixed composition ( p = 0.036) had a greater prevalence of complications than those with calculi of other compositions located in other sites. After a mean follow-up of 22.4 months no cases of ureteral strictures or vesicoureteral reflux were observed (Table). Discussion: The current findings support previous evidence showing safety and efficacy of RIRS with use of the UAS in pre-stented very young children. In our experience RIRS seems to be an effective and safe option with a stone-free rate of 81.3% and only 1 severe complication (Clavien–Dindo grade IIIb) and no long-term complications. This study is, to date, the first to examine the safety and efficacy of RIRS using UAS for the treatment of intrarenal stones in a selected cohort of pre-school patients weighing <20 kg. Conclusions: RIRS using UAS is an effective and safe procedure for treating kidney stones in pre-school patients weighing <20 kg without complications at both short and long term follow up. Stones of mixed composition located in the lower polar calices are associated with a greater risk of postoperative complications.